2022
DOI: 10.1158/1078-0432.ccr-22-2897
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Neutrophil-to-Lymphocyte Ratio and a New Inflammatory Biomarkers Prognostic Index for Primary Retroperitoneal Sarcomas: Retrospective Monocentric Study

Abstract: Purpose: Inflammatory biomarkers and neutrophil-to-lymphocyte ratio (NLR) are associated with prognosis in several tumors. Data on sarcomas are limited, and insufficient on retroperitoneal sarcoma (RPS). Experimental Design: Patients with primary RPS operated between 2002 and 2016 were included. Hemoglobin, monocytes, NLR, platelet-to-lymphocyte ratio (PLR) were retrieved and analyzed both individually and combined into a prognostic index (IBPI). Correlation with clinicopathologic variables was studied, as wel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In a study by Fiore et al [36 ▪▪ ], a significant correlation between NLR and survival was found within a large mono-institutional series of primary RPS (Table 2). Preoperative low hemoglobin, high percentage of monocytes, a high NLR, and a high platelet-to-lymphocyte ratio were associated with shorter OS in univariable Cox models.…”
Section: How To Improve Further Prognostication Of All Sarcomas: Inte...mentioning
confidence: 89%
“…In a study by Fiore et al [36 ▪▪ ], a significant correlation between NLR and survival was found within a large mono-institutional series of primary RPS (Table 2). Preoperative low hemoglobin, high percentage of monocytes, a high NLR, and a high platelet-to-lymphocyte ratio were associated with shorter OS in univariable Cox models.…”
Section: How To Improve Further Prognostication Of All Sarcomas: Inte...mentioning
confidence: 89%
“…NLR is an indicator of tumor-related inflammation and helps predict tumor prognosis[ 28 , 29 ]. In nivolumab-treated patients with HCC, dynamic changes in the NLR (at week 4) are effective prognostic indicators and may facilitate patient selection and subsequent clinical strategies for immunotherapies[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil-to-lymphocyte ratio (NLR) is an example of a serum inflammatory biomarker that has gained popularity as a prognostic measure in many cancers, including RPS [8,9 ▪ ]. An analysis of over 420 patients who underwent primary surgery for RPS demonstrated that NLR was an independent predictor of OS and improved the prognostic accuracy of Sarculator (a prognostic nomogram) [9 ▪ ]. Additional work on identifying a genomic signature that improves the performance of the Sarculator nomogram for patients with primary RPS was presented at the 2022 Connective Tissue Oncology Society meeting by Callegaro et al [10].…”
Section: Prognostic Toolsmentioning
confidence: 99%
“…Recently, efforts to further enhance the accuracy of these nomograms by integration of novel biomarkers and/or genomic signatures have been underway. The neutrophil-to-lymphocyte ratio (NLR) is an example of a serum inflammatory biomarker that has gained popularity as a prognostic measure in many cancers, including RPS [8,9 of the Sarculator nomogram for patients with primary RPS was presented at the 2022 Connective Tissue Oncology Society meeting by Callegaro et al [10]. As the discovery of novel biomarkers and genomic signatures continue to evolve, the possibility of incorporating these variables into existing prognostic nomograms for RPS holds promise to refine our ability to prognosticate and provide tailored treatment to patients undergoing surgery for primary RPS.…”
Section: Prognostic Toolsmentioning
confidence: 99%
See 1 more Smart Citation